Humidity Control for Air Circulation in the Drying Process - Aphisik Pakdeekaew; Krawee Treeamnuk; Tawarat Treeamnuk (Advances in Technology Innovation, 2023)
Recycling exhaust air is acknowledged as a method to reduce the energy consumption of agricultural products in the dryer. This study investigates the performance of an air circulation system at a laboratory scale and develops a feedback control compensator for optimizing the drying air circulation process. A servo motor is employed to drive a valve, to feed the exhaust drying air with high temperature and humidity back in different proportions. The system is controlled using an Arduino DUE microcontroller, which communicates data with MATLAB/Simulink. The system identification methodology is employed to analyze the mathematical model of the system. The result indicates that the response of the system meets the acceptance criteria when the percent overshoot is less than 25%, and the settling time is within 60 seconds (with a 2% error tolerance). Evaluation of control system performance during equilibrium employs R2 and RMSE values.